Proenkephalin system in human polymorphonuclear cells. Production and release of a novel 1.0-kD peptide derived from synenkephalin. - O Vindrola; M R Padrós; A Sterin-Prync; A Ase; S Finkielman; V Nahmod (The Journal of Clinical Investigation, 1990)
In the hematopoietic system a pluripotent stem cell generates precursors for lymphoid and myeloid lineages. Proenkephalin-derived peptides were previously detected in differentiated lymphoid cells. We have studied whether the proenkephalin system is expressed in a typical differentiated cell of the myeloid lineage, the neutrophil. Human peripheral polymorphonuclear cells contain and release proenkephalin-derived peptides. The opioid portion of proenkephalin (met-enkephalin-containing peptides) was incompletely processed, resulting in the absence of low molecular weight products. The nonopioid synenkephalin (proenkephalin 1-70) molecule was completely processed to a 1.0-kD peptide derived from the COOH-terminal. This molecule was characterized in neutrophils by biochemical and immunocytochemical methods. The chemotactic peptide FMLP and the calcium ionophore A23187 induced the release of the proenkephalin-derived peptides, and this effect was potentiated by cytochalasin B. The materials secreted were similar to those present in the cell, although in the supernatant a higher proportion corresponded to more processed products. The 1.0-kD peptide was detected in human, bovine, and rat neutrophils, but the chromatographic pattern of synenkephalin-derived peptides suggests a differential posttranslational processing among species. These findings demonstrate the existence of the proenkephalin system in human neutrophils and the production and release of a novel 1.0-kD peptide derived from the synenkephalin molecule. The presence of opioid peptides in neutrophils suggests their participation in the inflammatory process, including a local analgesic effect. Images